PerfIso: Performance isolation for commercial latency-sensitive services - Iorgulescu, Calin; Azimi, Reza; Kwon, Youngjin; Elnikety, Sameh; Syamala, Manoj; Tomita, Paulo; Narasayya, Vivek R.; Herodotou, Herodotos; Chen, Alex; Zhang, Jack; Wang, Junhua (My University, 2018)
Large commercial latency-sensitive services, such as web search, run on dedicated clusters provisioned for peak load to ensure responsiveness and tolerate data center outages. As a result, the average load is far lower than the peak load used for provisioning, leading to resource under-utilization. The idle resources can be used to run batch jobs, completing useful work and reducing overall data center provisioning costs. However, this is challenging in practice due to the complexity and stringent tail-latency requirements of latency-sensitive services. Left unmanaged, the competition for machine resources can lead to severe response-time degradation and unmet service-level objectives (SLOs). This work describes PerfIso, a performance isolation framework which has been used for nearly three years in Microsoft Bing, a major search engine, to colocate batch jobs with production latency-sensitive services on over 90,000 servers. We discuss the design and implementation of PerfIso, and conduct an experimental evaluation in a production environment. We show that colocating CPU-intensive jobs with latency-sensitive services increases average CPU utilization from 21% to 66% for off-peak load without impacting tail latency.
Keywords: CPU utilization; CPU-intensive; Machine resources; Production environments; Service level objective; Web searches; Search engines